Aesthetic Comprehension of Abstract and Emotion Concepts: Kant’s Aesthetics Renewed (Itinera, 2018)
In § 49 of the Critique of the Power of Judgment Kant puts forward a view that the feeling of pleasure in the experience of the beautiful can be stimulated not merely by perceptual properties, but by ideas and thoughts as well. The aim of this paper is to argue that aesthetic ideas fill in the emptiness that abstract and emotion concepts on their own would have without empirical intuitions. That is, aesthetic ideas make these concepts more accessible to us, by creating image schemas that allow us to think about these abstract concepts in a way linked to sensory experience, thereby imbuing them with a more substantive meaning and understanding.